Vitamin D status in Indian subjects: a retrospective analysis - Goel, Sanjiv (International Journal of Research in Orthopaedics, 2020)
Background: The objective of the study was to conduct a systematic evaluation of vitamin D status in pan India population, to provide a comprehensive depiction of the vitamin D status among Indians. Methods: This retrospective, cross-sectional, multicentric study considered data of subjects (≥18 years) who underwent 25(OH)D test at vitamin D screening camps, conducted at 229 sites across 81 cities in India. Primary study variables were proportion of subjects with vitamin D (25(OH)D) - severe deficiency (<5 ng/ml)/ deficiency (≥5-<20 ng/m)/ insufficiency (≥20-<30 ng/ml)/ sufficiency (≥30-<150 ng/ml) and toxicity (≥150 ng/ml). Results: Data from 4624 subjects (mean SD) age: 45.4 (14.5 years) was considered for this analysis. A total of 3552 (76.9%) subjects had vitamin D level of <30 ng/ml, including 41 (0.9%) subjects with severe deficiency, 2310 (50.0%) subjects with deficiency and 1201 (26.0%) subjects with insufficiency. Prevalence of vitamin D level of <30 ng/ml was found marginally higher in males (77.3%) than females (76.5%). Analysis of zonal data revealed that prevalence of vitamin D level <30 ng/ml was highest in east India (83.4%) followed by south (81.6%), west (76.3%) and north (73.3%). The incidence of vitamin D level <30 ng/ml was highest in the age-group of ≥18-≤30 years (82.5%), followed by >30-≤ 40 (80.4%), >40-≤50 (76%) and >50-≤65 (74.1%) years groups. Conclusions: Our study indicates a high prevalence of vitamin D deficiency/insufficiency in the Indian population irrespective of sex, age, and location. These clinically identified cases represent only a part of a bigger concern, necessitating the need for optimal public health action.